Kerjasama Pertahanan Indonesia-Korea Selatan: Kedaulatan Maritim dan Transfer Teknologi dalam Pengadaan Kapal Selam DSME 209/1400 - Faris Al-Fadhat; Naufal Nur Aziz Effendi (Jurnal Ketahanan Nasional, 2019)
ABSTRACT This study examined Indonesian defense cooperation with South Korea in producing DSME 209/1400 submarines and how its impact towards Indonesian broader defense and maritime policy. Indonesia was expected to had adequate defense equipment to covered its large geographical areas. Nevertheless, most of the national army’s defense equipment were old, while the domestic defenseindustry had just initiated. In this context, strategic cooperation was essential especially with countries which had advanced defense industries and technology. One example was Indonesian cooperation in submarine development with South Korea. This study used qualitative analytical methods by looking at the main driving factors, impacts, and complex challenges of Indonesian defense policy in the submarine sector.The results of this study showed that the Indonesia-South Korea cooperation was part of the country’s strategy to strengthened its submarines vision in 2024. In contrast to other existing cooperation which emphasizing on equipment trade, the agreement with South Korea had also initiated the process of technology transfer to helped Indonesian maritime defense for longer term. However, the findings of this study showed that the cooperation had serious challenges, especially with regards to human resources and budget allocation. ABSTRAK Penelitian ini bertujuan untuk mengkaji kebijakan kerjasama pertahanan Indonesia dengan Korea Selatan dalam hal pengadaan Kapal Selam DSME 209/1400 dan dampak yang ditimbulkan terhadap politik pertahanan dan maritim Indonesia. Sebagai negara yang menganut politik pertahanan defensif, Indonesiadituntutuntuk memiliki strategi alutsistayang sesuai dengan kondisi geografisnya. Sementara itu, pengembangan industri pertahanan nasional baru saja dimulai di tengah kondisi usia alutsista TNI yang sebagian besar sudah tua. Oleh karena itu, kerjasama dengan negara-negara yang memiliki industri pertahanan maju merupakan sebuah kebijakan strategis. Salah satunya adalahkerjasama Indonesia dengan Korea Selatan di bidang pengembangan kapal selam.Penelitian ini menggunakan metode kualitatif analitis dengan melihat faktor-faktor pendorong utama, dampak, serta tantangan yang cukup kompleks dari kebijakan pertahanan Indonesia di sektor kapal selam.Hasil dari penelitian ini menunjukkan bahwa kebijakan kerjasama Indonesia-Korea Selatan pada dasarnya merupakan upaya untuk memperkuat visi pengadaan kapal selam Indonesia pada tahun 2024. Berbeda dari beberapa kerjasama serupa yang bersifat pembelian alat pertahanan semata, kesepakatan yang ditandatangani tahun 2011 ini turut mengikusertakan proses transfer teknologi untuk menjamin keberlanjutan kemandirian maritim Indonesia. Meski demikian, temuan dalam